Retrospective evaluation of the use of autologous blood‐patch treatment for persistent pneumothorax in 8 dogs (2009–2012). (March 2014) - Oppenheimer, Nama; Klainbart, Sigal; Merbl, Yael; Bruchim, Yaron; Milgram, Josh; Kelmer, Efrat
Abstract Objective To describe the clinical course, outcome and success rate of 8 dogs with persistent pneumothorax treated with autologous blood‐patch pleurodesis (ABP). Design Retrospective case series. Setting University teaching hospital Animals Eight client‐owned dogs. Intervention Non‐coagulated blood was aseptically collected from the jugular vein and injected immediately into the pleural cavity of dogs with persistent pneumothorax. Measurements and Main Results The procedure was successful in 7 of 8 dogs. The median duration of pneumothorax until the ABP was performed was 4 days (range 2–6 days). Pneumothorax resolved immediately after 1 treatment in 4 dogs. Pleurodesis was repeated once in 3 dogs, and twice in 1 case after which it resolved in 3 of the 4 dogs. Out of a total of 13 ABP procedures performed in 8 dogs, 5 (62.5%) were successful after 1 procedure and the success rate increased to 87.5% after additional procedures. One dog failed ABP and was euthanized 3 days later due to continued deterioration and a hospital acquired pneumonia. Mild to moderate complications occurred in 2 other dogs and resolved in both. Conclusions ABP is a simple, inexpensive, and relatively safe procedure which can be considered in dogs with persistent pneumothorax that have failed conservative or surgical management. Infections following ABP were documented in 2 of the 8 dogs and resolved in 1 dog.